(untitled) (Web of Teachers: Inderscience Research, 2025)
It this paper we consider the important and modern methods of problem solving in physics teaching, namely, developing the form of physical thinking of students. Given the importance of problem solving in the study of physics, most students support the idea that the more problems, and especially difficult ones, are solved, the better. However, this puts a strain on the students, as a result of which they lose confidence in their abilities and the students lose interest in science. Therefore, today it is necessary to take a serious approach to the methodology of solving problems in physics.